2011
DOI: 10.1038/nrn2996
|View full text |Cite
|
Sign up to set email alerts
|

Second messengers and membrane trafficking direct and organize growth cone steering

Abstract: Graded distributions of extracellular cues guide developing axons toward their targets. A network of second messengers, Ca2+ and cyclic nucleotides, shapes cue-derived information into either attractive or repulsive signals that steer growth cones bidirectionally. Emerging evidence suggests that such guidance signals create a localized imbalance between exocytosis and endocytosis, which in turn redirects membrane, adhesion and cytoskeletal components asymmetrically across the growth cone to bias the direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
170
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 156 publications
(171 reference statements)
10
170
0
Order By: Relevance
“…Of particular interest is that chronically elevated cAMP levels can affect synaptic facilitation through effects on vesicular pools (54), and animals lacking AC8, which acts as a presynaptic calcium sensor, have WM but not long-term memory deficits (55), similar to Disc1 Tm1Kara animals. In that respect, it is noteworthy that cyclic nucleotide-dependent vesicle recycling at presynaptic terminals and growth cones has been implicated in both synaptic plasticity (24) and axon targeting (56) and therefore, is a potential link between these processes in Disc1 Tm1Kara animals. Along these lines, additional work needs to determine whether the volumetric change of synaptic vesicles in MFTs reflects abnormal cAMP-dependent vesicle recycling or biogenesis at the presynaptic terminal and whether it contributes to observed defects in synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is that chronically elevated cAMP levels can affect synaptic facilitation through effects on vesicular pools (54), and animals lacking AC8, which acts as a presynaptic calcium sensor, have WM but not long-term memory deficits (55), similar to Disc1 Tm1Kara animals. In that respect, it is noteworthy that cyclic nucleotide-dependent vesicle recycling at presynaptic terminals and growth cones has been implicated in both synaptic plasticity (24) and axon targeting (56) and therefore, is a potential link between these processes in Disc1 Tm1Kara animals. Along these lines, additional work needs to determine whether the volumetric change of synaptic vesicles in MFTs reflects abnormal cAMP-dependent vesicle recycling or biogenesis at the presynaptic terminal and whether it contributes to observed defects in synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Is PKA or Epac the cAMP effector in processes including initializing calcium entry via IICR [22] and VDCCs [21], and controlling the proposed attraction/repulsion switch [42,47]? Although the pathway and model for an attraction/repulsion switch [42,47] does not consider specific methods of calcium entry separately, it has been suggested that the method of entry affects the turning response [30,89]. Can this be understood only in terms of resulting calcium distributions?…”
Section: Box 3 Outstanding Questionsmentioning
confidence: 99%
“…[8][9][10] Furthermore, the growth cone has to be able to change its responsiveness to Netrin-1, leave the formerly attractive region of its intermediate target and continue growing towards its ultimate target. 7,11 For example, in the developing rat brain, commissural axons that are attracted by the floor plate cells secreting Netrin-1 lose their responsiveness to Netrin-1 after crossing the midline. 12 The same guidance molecule that initially drew the axon in is now perceived neutral or even as a repellent.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23] Downstream of the receptors the information is relayed to Ca 2+ and cAMP/cGMP second messenger systems. 24 Exposing a growth cone to a concentration gradient of attractive or repulsive guidance cue induces an asymmetric elevation of [Ca 2+ ] i , 11 where the initial level and source of Ca 2+ regulate the response to Netrin-1. [16][17] The attractive signaling involves activation of two plasma membrane cation channels, transient receptor potential cation channel subfamily C (TRPC) and L-type voltage-dependent Ca 2+ channel (LVDCC), as well as the release of Ca 2+ from the endoplasmic reticulum (ER) through ryanodine channels (RyRs).…”
Section: Introductionmentioning
confidence: 99%